Effects of Low Levels of Zinc on the Ovarian Development of Tilapia nilotica Linnaeus - Cariño, Virginia; Cruz, Noel (Science Diliman: A Journal of Pure and Applied Sciences; Vol 3 (1990), 2007)
Eight to ten days posthatch fry of Tilapia nilotica Linn. were exposed to sublethal levels of zinc, 2 mg/l and 5 mg/l. After 30 days, ovarian differentiation occurred in the unexposed fry while gonadal anlage of zinc-exposed fry contained still undifferentiated primordial germ cells (PGC). Normal oogenesis was exhibited by the unexposed ovaries after 57 days. Zinc caused alterations in the egg membrane layers. Histopathological changes as degeneration and hyperemia in treated ovaries were observed under the light and electron microscope.